Expressions and stylistic trends of homeowners in terrace housing / Masran Saruwono, Abdurrahman Mohd Rashdi and Erdayu Os'hara Omar - Saruwono, Masran; Mohd Rashdi, Abdurrahman; Os'hara Omar, Erdayu (Faculty of Architecture, Planning and Surveying, 2012)
This study attempts to discover the alteration trends of house renovations focusing on terrace houses. Thirty renovated houses located in Shah Alam were identified visually observed and analysed. The houses were photographed and sorting process was carried out for analysis at the studio. The results show the altered houses could be classifed into four stablished styles namely; traditional, modern, post-modern and "others". There is no one particular style of facade that was signifantly more popular among them. Something that can be learnt from this study is that people re expressive of their stylistic preferences even under the constraints of he typically narrow-frontaged terrace houses.